Otimização da pegada de carbono em abordagem multicritério de dosagem de concreto - Padilha Júnior, Marcos Antonio (2022)
The preservation of the environment has become the subject of several discussions in recent decades, man being a modifying agent of this, is closely linked to the actions of environmental degradation. For this reason, industrial production processes are undergoing changes with a view to sustainable development, with the construction industry is no different, it is seen as one of the ones that generates the most compounds linked to global warming, as in the case of carbon dioxide. (CO2). Concrete is referenced by many authors as the most used construction material in the world, linked to its composition we have cement, which alone is responsible for about 36% of all CO2 generated by construction activities. Although studies are on the agenda aimed at reducing cement consumption or replacing it with other materials with equivalent properties, the concrete mixing processes currently used do not take into account the carbon footprint (eCO2) which is the equivalent carbon emission emitted into the atmosphere generated in the process. This work analyzed several methodologies applied in concrete mixing processes, from classical processes to refined and updated processes, with approaches in particle packing processes. In this way, a methodology was proposed for evaluating concrete mixtures in an integrative way, which aggregates multiple technical, economic and environmental parameters, with a focus on minimizing the carbon footprint. To this end, 04 variables were defined: Mechanical, Durability, Environmental and Economic for the implementation of the model, later, it was followed by the calibration and validation steps. In the calibration stage, the American Concrete Institute method was chosen for the dosage of concrete mixtures, with strengths varying between 15 and 40 MPa, slump of 100 mm and with variations in the sizes of coarse and fine aggregates, thus obtaining 416 projects of dosage, with these data the relative costs were computed based on a unit price composition used for ready-mixed concrete from the National Department of Transport Infrastructure - DNIT, the carbon footprint was calculated using the OpenLCA tool with the database In order to improve the data from Ecoinvent 3.7, particle packing concepts were introduced using classical methods and the compressible packing method. For model validation, 180 concrete mixtures were analyzed with dosages obtained from works in the literature, later, another 24 mixtures obtained with a Brazilian company of national scope were analyzed and another 04 mixing projects carried out by the author of this work. The data obtained point to a potential use of the integrator model of multiple parameters, in the analysis of projects of concrete mixtures, in order to minimize the carbon footprint.